DESIGN, FABRICATION AND TESTINGOF COMPOSITE MONO LEAF SPRING - Mr. G.R.Deshpande; Mr.Pravin Gundala; Mr. Kaustubh Deshpande; Mr. Swapnil Bhosale (International Journal of Innovations in Engineering Research and Technology, 2021)
Originally called laminated or carriage spring, a leaf spring is a simple form of spring, commonly used for the suspension in wheeled vehicles.For very heavy vehicles, a leaf spring can be made from several leaves stacked on top of each other in several layersused in the rear suspension systemof a light duty vehicle is analyzed by finite elementmethod using ANSYS software,often with progressively shorter leaves. A leaf spring can either be attached directly to the frame at both ends or attached directly at one end, usually the front, with the other end attached through a shackle, a short swinging arm. The shackle takes up the tendency of the leaf spring to elongate when compressed and thus makes for softer springiness.Theautomobile industry has shown increased interest in the use of composite leaf spring in the place of conventional steel leaf spring due to high strength to weight ratio.To conserve the natural resources and economize energy, weight reduction has been the main focus of automobile manufacturer in the present scenario. Actually, there is almost a direct proportionality between the weight of the vehicle and its fuel consumption, particularly in city driving. The advanced composite materials such as Graphite, Carbon, Kevlar and Glass with suitable resins are widely used because of their high specific strength (strength/density) and high specific modulus (modulus/density). Advanced composite materials seem ideally suited for suspension (leaf spring) applications.